Die Schriften des Johannes von Damaskos - John, of Damascus, Saint (Patristische Texte und Studien, 1969)
Critical edition of the Greek monastic romance Barlaam and Josaphat, traditionally ascribed to St John Damascene, in reality however a work from the late 10th cent., in all probability composed by the Georgian abbot Euthymios from Mount Athos.